Corporate Sustainability And Company Performance: A Review Paper (International Journal of Innovative Research in Engineering & Management, 2021)
A complete article each planning authorities was a paper that  was printed in a few of the scientific papers. Articles and books  were divided into separate categories based on a variety of  criteria. There were a record of 101 scientific journal resources  assessed. scored based on the nature of the study, the depth of  analysis, and the applicability. The study shows that the majority  of research on the connection between sustainability  performance and business success has focused on developed  nations. The outcome varies depending on the cultural and  economic environment, and there is no generally acceptable  relationship orientation. In recent years, research contributions  have shown a trend of increase. In most studies, financial  performance is employed as a proxy for company performance.  As previously said, the many study gaps may be utilized for  future research. It also believes that in developing nations, more  is there a need for further research on the link across corporate  social responsibility (csr and company performance. The  findings of this research will only be applicable to a subset of  public resources utilized for a specific timeframe, not to  everyone in the number of studies addressing csr practices. In terms of numerous factors, there may be many unexplored  regions for future study. This article fills a gap in the literature  on corporate sustainability performance evaluation by providing  a thorough analysis.
Keywords: Firm Performance; Management; Sustainable Development; Sustainability Performance